Reorientasi Hukum Keluarga Islam Perspektif Para Guru Besar UIN di Indonesia - Andi Iswandi (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2021)
This study aims to analyze the views of Islamic academics, especially the professors of the State Islamic University in Indonesia (Muhammad Amin Suma, Musdah Mulia, M. Amin Abdullah, and Sahiron Syamsudin) regarding their views in seeing the reality of Islamic Family Law in Indonesia from time to time. This study uses a descriptive normative and legal literature review approach, namely a description of the current situation regarding the views of academics in Islamic legal research. This research leads to the conclusion that the formation of the Islamic Law Compilation is responsible and consistent. Reorientation of Islamic Family Law is a necessity for a pluralistic Indonesian society and is constantly developing. Compilation of modern Islamic law and maintaining Indonesian culture with dignity becomes an integrated and interconnective Madani KHI between classical KHI, CLD-KHI, and RUU-HMPA. When this happens, the taqninization (Islamization) of national law will be realized.